Use of Student Evaluation of Teaching (SET) Survey to Evaluate Effectiveness of Teaching in a Leadership Course among Dental Students over Three Years. (1st June 2020) - Nazir, Muhammad; Al-Ansari, Asim; AlKhalifa, Khalifa; Gaffar, Balgis; AlHumaid, Jehan
Abstract : Leadership courses are being increasingly integrated into dental curricula. The study aimed to assess the validity and reliability of student evaluation of teaching (SET) instrument among dental students and to evaluate the effectiveness of teaching in a new leadership course over a period of three years. This cross-sectional study was conducted on fourth-year undergraduate dental students ( N  = 260) who took a practice management course over three consecutive years from 2014 to 2016. A 29-item SET questionnaire was administered among students who were willing to participate in the study. Out of 260 students, 185 returned completed surveys and the response rate was 71.15%. Factor analysis (principal component analysis) showed the validity of four dimensions of the SET instrument. Total variance explained by four dimensions was 62.80%. Cronbach's alpha for the instrument was 0.95 and each dimension had fairly high internal consistency (>0.80). Treating students with respect (94%), accepting different viewpoints of students (94.1%), being flexible/open-minded (92.5%), and preparedness in the course (91.9%) were the most common effective teaching traits. Over the period of three years, 16 items showed improvement in teaching and there was a significant improvement in four items (P < 0.05 ). In conclusion, it was found that SET is a valid instrument to evaluate the effectiveness of teaching in nonclinical courses in dentistry. This instrument should be used longitudinally to compare the effectiveness of teaching.